The Contribution of the First Female Pharmacists to the Development of Pharmaceutical Services in Zrenjanin - Radoš, Ljubica; Krajnović, Dušanka (Archives of Pharmacy, 2022)
Nowadays, women dominate pharmacy. They received the permission to study and run a pharmacy around the end of the 19th and beginning of the 20th century. We aimed to present the position and life path of the first female pharmacists on the territory of today's municipality of Zrenjanin. Documentary and historical analysis were applied. Universities in the area of today's Vojvodina admitted women to study pharmacy in Budapest in 1895, and in Austria in 1900. The first female owner of a pharmacy in Vojvodina was Ilona Halmoš Sege, who graduated in 1908 in Budapest. She opened her first pharmacy "Kod Svetog Stevana" in Šupljaja in 1913, and she moved to Petrovgrad (Zrenjanin) in 1918, where she bought the pharmacy "Kod krune". In the interwar period mutual struggles of pharmacy owners for customers, complaints and disagreements. Another female pharmacist, Vera Nikolić, who was the daughter of Emil Nikolić, a pharmacist and owner of the pharmacy "Kod anđela", took over the pharmacy from her father in the interwar period. She led it until its nationalization in the 1950s, when her pharmacy became a state pharmacy , and she worked as a pharmacist until her retirement. The first women in pharmacy in Zrenjanin worked, fought with the competition, and survived as the owners of pharmacies for more decades, but their work was interrupted by historical war circumstances. Although in the minority, they developed and maintained apothecary profession and thus contributed to the development of healthcare in this part of the Banat.